1977
DOI: 10.2134/agronj1977.00021962006900020009x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Water‐Root Relations in Wheat: Water Extraction Rate of Wheat Roots that Developed under Dry and Moist Conditions1

Abstract: Prior investigations have reported modifications of various root characters of plants grown under relatively dry soil conditions, but there is a lack of information on the effect of these modifications on the capacity of root systems to extract soil water. This study was therefore conducted to investigate whether the root systems of wheat (Triticum aestivum L.) grown under different soil water conditions differed in their capacity to extract water from the soil. In a greenhouse experiment the water extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 3 publications
2
15
0
Order By: Relevance
“…Other reports of increased lateral root proliferation (e.g. Sharma & Ghildyal, 1977;Osonubi & Davies, 1978;Huck et al, 1983) in response to drought have commonly used considerably higher soil water potentials than those used in the present study. This information therefore appears to be the first to suggest that roots may respond to a severe drought by producing new lateral roots at SMPs as low as -6 to -8 MPa.…”
Section: Discussionmentioning
confidence: 95%
“…Other reports of increased lateral root proliferation (e.g. Sharma & Ghildyal, 1977;Osonubi & Davies, 1978;Huck et al, 1983) in response to drought have commonly used considerably higher soil water potentials than those used in the present study. This information therefore appears to be the first to suggest that roots may respond to a severe drought by producing new lateral roots at SMPs as low as -6 to -8 MPa.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, a vigorous shallow root system is required for absorption of nutrients that are mostly concentrated in the upper layers of soil (Manske and Vlek 2002). Increases in root system traits in response to drought stress were first reported in plants by Muller-Thurgau (1875); and subsequently there were specific reports for maize (Zea mays L.) (Sharp and Davies 1979), wheat (Sharma and Ghildyal 1977), and soybean (Glycine max L.) (Huck et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Schurmann (1959) and Proffitt et al (1985) reported that when water supply in the upper soil profile was plentiful, rooting depth remained shallow. Sharma and Ghildyal (1977) observed that drier soil conditions promoted root elongation and increased the degree of branching, allowing the crop to exploit soil water more completely. However, Barraclough et al (1989) reported that wheat crops do not necessarily exhaust all available soil water before commencing uptake from the next deeper layer.…”
mentioning
confidence: 98%